Principios de Medición Multidimensional de la Pobreza - Boltvinik, Julio (La Sociología en sus Escenarios, 2010)
Abstract. Principles of Multidimensional Measurement of the Poverty The multidimensional measurement of the poverty faces (among others) the problem of the apparent heterogeneity between dimensions of the well-being, which is derived from the multiplicity of the human needs, satisfactores and well-being sources. This is associate to the limits of the market, to the fact that the values of change they are not universal, that all the valuable one for the human well-being cannot be bought, that everything does not have price. Principle of poverty it means like standard of life principle: Its means, basically, that we use the same concept of well-Being - that we applied in the study of the standard of life (NV) and that, therefore, we rejected the position of Sen and Foster which they have defined the elementary poverty like "deprivation of minimum capabilities and social abilities". Meaning that the poverty is not equivalent to a Standard of life underneath a threshold but, between the capabilities and abilities that are used to study the NV we chose only the elementary minims and to study the poverty, breaking with the unitary criterion of the species homo sapiens, classifying to the poor men like citizens of second class who, when much, would aspire to reach the minimum capabilities and the elementary social abilities. Resumen. Principios de Medición Multidimensional de la Pobreza La medición multidimensional de la pobreza enfrenta (entre otros) el problema de la heterogeneidad aparente entre dimensiones del bien-estar, lo que se deriva de la multiplicidad de las necesidades humanas, satisfactores y fuentes de bien-estar. Esto está asociado a los límites del mercado, al hecho de que los valores de cambio no son universales, que no todo lo valioso para el bien-estar humano se puede comprar, que no todo tiene precio. Principio de pobreza como parte del nivel de vida Este principio significa, básicamente, que en el estudio de la pobreza partimos del mismo concepto de Bien -Estar que aplicamos en el estudio del nivel de vida (NV) y que, por tanto, rechazamos la postura de Sen y Foster que han definido la pobreza como "privación de capabilities mínimas y habilidades sociales elementales". Es decir que la pobreza no es equivalente a un Nivel de Vida debajo de un umbral sino que, entre las capabilities y habilidades que se utilizan para estudiar el NV elegimos sólo las mínimas y elementales para estudiar la pobreza, rompiendo con el criterio unitario de la especie homo sapiens, clasificando a los pobres como ciudadanos de segunda que, cuando mucho, aspirarían a alcanzar las capabilities mínimas y las habilidades sociales elementales.